2012
DOI: 10.1186/gb-2012-13-8-r75
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of long non-coding RNAs and novel transcribed regions across a diverse panel of archived human cancers

Abstract: BackgroundMolecular characterization of tumors has been critical for identifying important genes in cancer biology and for improving tumor classification and diagnosis. Long non-coding RNAs, as a new, relatively unstudied class of transcripts, provide a rich opportunity to identify both functional drivers and cancer-type-specific biomarkers. However, despite the potential importance of long non-coding RNAs to the cancer field, no comprehensive survey of long non-coding RNA expression across various cancers has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
173
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(174 citation statements)
references
References 28 publications
1
173
0
Order By: Relevance
“…51 In our study, a number of the top hits across multiple sarcoma subtypes were lncRNAs, including D21S2088E in angiosarcoma and PCGEM1 in Ewing's sarcoma, both of which were the most significantly upregulated transcripts relative to all of our other samples. PCGEM1 is normally expressed only in prostate tissue; significant upregulation of PCGEM1 is an established biomarker for prostate cancer.…”
Section: Therapeutic Targets In Human Soft Tissue Tumors Ae Sarver Et Almentioning
confidence: 61%
“…51 In our study, a number of the top hits across multiple sarcoma subtypes were lncRNAs, including D21S2088E in angiosarcoma and PCGEM1 in Ewing's sarcoma, both of which were the most significantly upregulated transcripts relative to all of our other samples. PCGEM1 is normally expressed only in prostate tissue; significant upregulation of PCGEM1 is an established biomarker for prostate cancer.…”
Section: Therapeutic Targets In Human Soft Tissue Tumors Ae Sarver Et Almentioning
confidence: 61%
“…Previous studies have demonstrated that the expression of lncRNAs is dysregulated in a variety of human cancers, and these aberrant lncRNAs may serve key roles during the initiation and progression of cancer (12)(13)(14). However, lncRNA research remains premature when compared to what is understood about protein-coding RNA and microRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Using a range of techniques, such as microarray, 18 RNA sequencing, 19 and real-time PCR, 20 many studies have confirmed that lncRNA expression levels differ between normal and tumor tissues and vary among tumor types. [21][22][23] Although some of these abnormal expression patterns may be secondary effects from the cancer transformation, several factors suggest that lncRNAs could influence tumorigenesis. These factors include the tremendous complexity and diversity of the lncRNA landscape, the finding that lncRNAs are often located at crucial sites (eg, regions of singlenucleotide polymorphisms (SNPs), amplifications, or at common breakpoints), the presence of sequence motifs and other elements that result in specific structures, their regulation, and their functional relationships with other nucleic acids and proteins.…”
Section: Lncrnas In Cancermentioning
confidence: 99%